2016
DOI: 10.17756/jnpn.2016-009
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Hyperintensities in Older Adults and Motoric Cognitive Risk Syndrome

Abstract: Introduction Motoric cognitive risk (MCR) syndrome is a recently described pre-dementia syndrome characterized by slow gait and cognitive complaints that has been implicated as a predictor of cognitive decline and dementia in older adults. Previous work suggests that cerebrovascular disease is associated with MCR. White matter hyperintensities (WMH) are postulated to be a product of cerebrovascular disease, and have been associated with impaired mobility and impaired cognition. This study aimed to determine if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 53 publications
(75 reference statements)
2
17
0
Order By: Relevance
“…It was characterized by smaller volumes of total gray matter, total cortical gray matter, premotor cortex, prefrontal cortex especially dorsolateral segment, but no significant differences were obtained in terms of the volumes of hippocampal and white matter [48,49], which are in concordance with these results as the two components of MCR controlling cognitive complaints and slow gait. MCR related brain regions reduction contributes to predict cortical neurodegenerative dementia more than subcortical dementia such as vascular dementia [48].…”
Section: Discussionsupporting
confidence: 77%
“…It was characterized by smaller volumes of total gray matter, total cortical gray matter, premotor cortex, prefrontal cortex especially dorsolateral segment, but no significant differences were obtained in terms of the volumes of hippocampal and white matter [48,49], which are in concordance with these results as the two components of MCR controlling cognitive complaints and slow gait. MCR related brain regions reduction contributes to predict cortical neurodegenerative dementia more than subcortical dementia such as vascular dementia [48].…”
Section: Discussionsupporting
confidence: 77%
“…It was characterized by smaller volumes of total gray matter, total cortical gray matter, premotor cortex, prefrontal cortex especially dorsolateral segment, but no significant differences were obtained in terms of the volumes of hippocampal and white matter [44,45], which are in concordance with these results as the two components of MCR controlling cognitive complaints and slow gait. MCR related brain regions reduction contributes to predict cortical neurodegenerative dementia more than subcortical dementia such as vascular dementia [44].…”
Section: Discussionsupporting
confidence: 77%
“…Studies have shown that MCR involves a wider range of brain regions and that its involvement is not limited to the hippocampus, which is a key brain region for memory and spatial navigation processes [46][47][48]. MCR has been characterized by smaller volumes of total grey matter, total cortical grey matter, the premotor cortex, and the prefrontal cortex, especially the dorsolateral segment; however, no significant differences were found in terms of the volumes of hippocampal and white matter [49,50], which is in concordance with these results as these two components control cognitive complaints and slow gait. MCR-related brain region reduction contributes more to the prediction of cortical neurodegenerative dementia than that of subcortical dementia, such as vascular dementia [49].…”
Section: Discussionmentioning
confidence: 99%